Analisis Kelayakan Investasi Pada Pit 2 Nambalau Tambang Batukapur PT. Bakapindo Jorong Durian Kenagarian Kamang Mudiak Kecamatan Kamang Magek Kabupaten Agam Provinsi Sumatera Barat - Ferdi Domala Pani; Tri Gamela Saldy (Journals Mining Engineering : Bina Tambang, 2021)
PT. Bakapindo is a private mining company engaged in limestone mining, currently planning a new land clearing called Pit 2 Nambalau. This area has an area of 15 hectares, with a total exploration reserve of 10,315,455.50 tons and a production target of 300,000 tons per year. However, from the results of field observations, it was found that there was no grouping of cash in and cash out budgets and there was no investment feasibility study at Pit 2 Nambalau, therefore, NPV, BCR and PP methods were used to obtain an investment feasibility study. The method used in conducting this research uses the type of quantitative research. This is because in future research, data will be used in the form of numbers. The research was conducted by grouping cash flows both with tables and graphics, calculating the NPV value, calculating the BCR value, calculating the PP value, and calculating the MF of the digging and loading equipment. Based on the results of the research that the author did using 3 cash flow designs, the NPV value was Rp. 671.112.469.799,- with BCR of 3.561 and PBP for 1.12 years on cash flow A, which is cash flow with gradient costs and gradient benefits increasing. Meanwhile, in cash flow B with an increasing gradient of benefits, the NPV value is Rp. 766.820.708.490,- with a BCR of 5.63 and a PBP of 1.09 years. Meanwhile, in cash flow C with an increasing cost gradient, the NPV value is Rp. 261.459.829.799, - with a BCR of 2.00 and a PBP of 1.24 years. So based on the calculations that have been done, it can be concluded that pit 2 Nambalau is economically feasible to mine. And for the MF value obtained 0.88 with the need for 1 unit of excavator and 2 units of dumptruck.